2006
DOI: 10.1364/ao.45.001375
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride antireflection coatings for deep ultraviolet optics deposited by ion-beam sputtering

Abstract: Optically high quality coatings of fluoride materials are required in deep ultraviolet (DUV) lithography. We have applied ion-beam sputtering (IBS) to obtain fluoride films with smooth surfaces. The extinction coefficients were of the order of 10(-4) at the wavelength of 193 nm due to the reduction of their absorption loss. The transmittance of the MgF2/GdF3 antireflection coating was as high as 99.7% at the wavelength of 193 nm. The surfaces of the IBS deposited films were so smooth that the surface roughness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 8 publications
0
23
0
Order By: Relevance
“…However, actually any thin film has certain surface roughness. In some applications, this roughness has a very important influence on its optical characteristics, such as deep-ultraviolet sculpture [1], ring lasers [2], gravitational wave detectors [3], etc. Therefore, it is important to establish a theoretical analysis model of multilayer optical characteristics when considering surface roughness.…”
Section: Introductionmentioning
confidence: 99%
“…However, actually any thin film has certain surface roughness. In some applications, this roughness has a very important influence on its optical characteristics, such as deep-ultraviolet sculpture [1], ring lasers [2], gravitational wave detectors [3], etc. Therefore, it is important to establish a theoretical analysis model of multilayer optical characteristics when considering surface roughness.…”
Section: Introductionmentioning
confidence: 99%
“…Among the very limited number of materials, besides LaF 3 , GdF 3 is a potential high refractive index candidate for further development in the excimer laser application area. Furthermore, these fluoride materials have the potential for application in the UV region down to 130 nm [3,6]. It was shown that the least amount of optical loss of the fluoride can be obtained by resistive heating evaporation.…”
Section: Introductionmentioning
confidence: 99%
“…Because the lowest refractive indices for dielectrics are above 1.35, bulk materials cannot attain this value. Therefore, many effective approaches based on gratings [1], etching or leaching of glass [2,3], sol-gel synthesis [4], sputtering [5], phase separation and selective dissolution [6], and dip coating of particles [7] are proposed to achieve low-index materials. However, to realize broadband antireflection, multilayer coatings with different index should be used for reducing reflection of different wavelength [8].…”
Section: Introductionmentioning
confidence: 99%